ANALYSING AND MAPPING OF LAND FIRE VULNERABILITY IN KUMPEH, MUARO JAMBI DISTRICT, JAMBI PROVINCE - Farhan Kurniawan; Idung Risdiyanto; Ana Turyanti (Sociae Polites, 2020)
Forest and land fires have become disasters that have received international attention. Peatland as an important part of the forest poses a separate threat to the effect of carbon release and climate change. Fire prevention can be done by understanding the causes. Fire vulnerability mapping uses several parameters in its calculation, namely NDVI value, NDMI value, TWI value, accessibility distance, and community activity center. Land use and hotspot history will be the parameters compared with the results of the analysis. The calculation uses a range of values ​​from 1 to 5. The risk level class is divided into five, with the highest percentage of 20.18% at the very vulnerable level and the lowest of 19.56% at the normal level. Very vulnerable areas have the highest number of hotspot points at 268 points while the lowest number of hotspot points is in the safe class of 23 points. Most areas with high vulnerability are found in agriculture and plantation areas. The model used in this fire vulnerability map can be said to have a pretty good correlation. Keywords: accessibility distance, forest fires, hotspot, land use, peatland